Brain functional alterations in early stage of coal workers’ pneumoconiosis with alcoholism: insights from a resting-state fMRI investigation - Boting Xue; Gang Cao; Lingling Ren; Yuxiang Zhao; Xuecong Lv; Yong’ai Li; Hagiwara Akifumi; Hagiwara Akifumi; Yongbo Liu; Xiaowei Han (Frontiers in Neuroscience)
ObjectivesThis study aimed to investigate resting-state functional magnetic resonance imaging (fMRI) changes in Coal Workers’ Pneumoconiosis (CWP) patients with alcoholism using Amplitude of Low-Frequency Fluctuation (ALFF) and Functional Connectivity (FC) analyses.Materials and methodsA total of 60 patients with stage I CWP and 30 healthy controls were prospectively enrolled. The CWP patients were further divided into drinking and non-drinking groups. Resting-state fMRI scans were performed for all three groups, and correlations between abnormal ALFF signals, FC changes, and clinical baseline data were analyzed.ResultsCompared to the control group, both the CWP drinking and non-drinking groups exhibited increased ALFF signals in the left orbitofrontal cortex, left frontal pole, right intracalcarine cortex, and right precuneus cortex, as well as decreased ALFF signals in the bilateral temporal pole and left occipital fusiform gyrus. Functional connectivity analysis revealed increased connectivity from the right orbitofrontal cortex to the right pars triangularis of the inferior frontal gyrus and from the right precuneus cortex to the right lingual gyrus in both CWP groups. Conversely, decreased connectivity was observed in the left and right frontal poles. Additionally, a positive correlation was found between ALFF values in the left temporal pole and PaO2 levels in the CWP drinking group (r = 0.369, p = 0.038). In the CWP non-drinking group, functional connectivity between the right precuneus cortex and the right lingual gyrus showed a negative correlation with FVC (r = −0.442, p = 0.027).ConclusionCWP patients with alcoholism exhibit abnormal brain regions and functional connectivity associated with spontaneous neural activity changes. Significant correlations between specific brain regions and clinical indicators were identified. These findings provide a foundation for understanding neuroimaging changes in CWP patients with alcoholism through fMRI.